Media Komik Pada Pelajaran IPA Untuk Meningkatkan Multiple Intelligences Siswa SD - Yuliariatiningsih, Margaretha Sri (Universitas Pendidikan Indonesia, 2010)
AbstractThis study was grounded on the students’ hobby in reading comics. The result of the literature study showed that comic used as media in learning Physics was very effective as learning media and attractive to be read. One of the supporting factors of this success in improving the students’ multiple intelligences was the integration of art and craft activities in the science learning process. Moreover, the theory of multiple intelligences accomodated students with various way of learning thinking. The developed training model in this study consisted of five stages that were orientation, presentation, structured excersice, guided excersice and individual excersice. In each Science class, the learning process was always started with the elicitation of students’ prior knowledge. Then each student got one comic to be read. After the reading session, the teacher asked them about the contents of the comics either classically or individually. In the next step the students were invited to observe the demonstration done by the teacher only if the instruments or materials were not safe for them, (e.g hot water). Nevertheless, if they were safe enough for the students, they were allowed to do the experiment by themselves. Students’ worksheets (LKS) were done by the students in group to develop their interpersonal and verbal-linguistic intelligences. Based on observation during experiments and drawing activities, the students’ visual-spatial intelligences were developed. Every learning process was always ended with knowledge test individually which would be discussed later. The study concluded that: 1) the training model improved PGSD students’ skills in developing comic as teaching media, 2) comics are proven to improve the elementary school students’ motivation in learning science, 3) comic enhanced elementary school students’ understanding in science knowledge which was indicated by the achievement of the students’ test score (85 point grade). Comic also developed elementary school students’ multiple intelligences in the aspects of verbal-linguistic, logical-mathematic, visual-spatial, naturalist, and interpersonal. It is recommended that comic should be developed as teaching media especially in elementary school. Comis can be used as one alternative of learning medias that can motivate students to learn something as well as improving their reading hobby. Key Word: comic, motivation, learning science, achievement